2022
DOI: 10.3389/fcimb.2021.808550
|View full text |Cite
|
Sign up to set email alerts
|

Phase Variation of LPS and Capsule Is Responsible for Stochastic Biofilm Formation in Francisella tularensis

Abstract: Biofilms have been established as an important lifestyle for bacteria in nature as these structured communities often enable survivability and persistence in a multitude of environments. Francisella tularensis is a facultative intracellular Gram-negative bacterium found throughout much of the northern hemisphere. However, biofilm formation remains understudied and poorly understood in F. tularensis as non-substantial biofilms are typically observed in vitro by the clinically relevant subspecies F. tularensis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 84 publications
(131 reference statements)
1
25
0
Order By: Relevance
“…Highlighting the differences in biofilm formation among F. tularensis subspecies, O-Ag mutants in F. novicida form biofilms that are equal or less than the parental wild-type (Champion et al, 2019). Mlynek et al identified a link between variation of the O-Ag and biofilm formation in F. tularensis (Mlynek et al, 2021). In agreement with the Champion findings, biofilm formation typically required at least 7 days to occur.…”
Section: O-antigen Influences the Biofilm-forming Capacity Of Francis...mentioning
confidence: 75%
See 4 more Smart Citations
“…Highlighting the differences in biofilm formation among F. tularensis subspecies, O-Ag mutants in F. novicida form biofilms that are equal or less than the parental wild-type (Champion et al, 2019). Mlynek et al identified a link between variation of the O-Ag and biofilm formation in F. tularensis (Mlynek et al, 2021). In agreement with the Champion findings, biofilm formation typically required at least 7 days to occur.…”
Section: O-antigen Influences the Biofilm-forming Capacity Of Francis...mentioning
confidence: 75%
“…Francisella species have been shown to form biofilm [reviewed by van Hoek (2013) ], though clinically important subspecies of F. tularensis tend to form a less defined biofilm with sparse cell density than F. novicida or other Francisella species( Margolis et al, 2010 ; Mahajan et al, 2011 ). Recent studies demonstrate that O-antigen (O-Ag) of the LPS can influence the biofilm-forming capacity of Type A and B isolates, changing this perception of biofilm formation in F. tularensis ( Champion et al, 2019 ; Mlynek et al, 2021 ). This review aims to explore where phase variation and biofilm may play a role in the survival and pathogenesis of F. tularensis which could lead to new therapies to prevent disease.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations